Comparison of the connectivity of the posterior intralaminar thalamic nucleus and peripeduncular nucleus in rats and mice - Cai, Hui-Ru; Chen, Sheng-Qiang; Xiang, Xiao-Jun; Zhang, Xue-Qin; Ma, Run-Zhe; Zhu, Ge; Ding, Song-Lin (Frontiers in Neural Circuits, 2024)
The posterior intralaminar thalamic nucleus (PIL) and peduncular nucleus (PP) are two adjoining structures located medioventral to the medial geniculate nucleus. The PIL-PP region plays important roles in auditory fear conditioning and in social, maternal and sexual behaviors. Previous studies often lumped the PIL and PP into single entity, and therefore it is not known if they have common and/or different brain-wide connections. In this study, we investigate brain-wide efferent and afferent projections of the PIL and PP using reliable anterograde and retrograde tracing methods. Both PIL and PP project strongly to lateral, medial and anterior basomedial amygdaloid nuclei, posteroventral striatum (putamen and external globus pallidus), amygdalostriatal transition area, zona incerta, superior and inferior colliculi and the ectorhinal cortex. However, the PP rather than the PIL send stronger projections to the hypothalamic regions such as preoptic area/nucleus, anterior hypothalamic nucleus and ventromedial nucleus of hypothalamus. As for the afferent projections, both PIL and PP receive multimodal information from auditory (inferior colliculus, superior olivary nucleus, nucleus of lateral lemniscus and association auditory cortex), visual (superior colliculus and ectorhinal cortex), somatosensory (gracile and cuneate nuclei), motor (external globus pallidus) and limbic (central amygdaloid nucleus, hypothalamus, and insular cortex) structures. However, the PP rather than PIL receives strong projections from the visual related structure parabigeminal nucleus. The results from Cre-dependent viral tracing in mice have also confirmed the main results in rats. Together, the findings in this study would provide new insights into the neural circuits and functional correlation of the PIL and PP.